Development and Application of an Analytical Model for Horizontally Curved Bridge Decks. Issue 1 (January 2015) - Fatemi, S.J.; Sheikh, A.H.; Ali, M.S. Mohamed
This paper presents a reliable closed form analytical solution without any major simplification which can be used with confidence by designers for the analysis of statically indeterminate horizontally curved bridges idealized as curved girders. The unit load method, a method extracted from the Castigliano's second theorem is used to derive the proposed closed form analytical solution which is then used to obtain the influence line diagram of shear force, bending moment and torsion of the curved bridge girder and it is validated with the published test results and also with the finite element solution of a curved girder. Moreover, an extensive parametric study is conducted using the proposed analytical model to investigate the effect of various parameters such as curvature ratio, span length, number of cells and number of loading lanes on bending moment and torsion of the curved bridges subjected to Australian bridge design loads where the effect of all these parameters except the number of cells is found to be significant. Finally, a comparative study of the behaviour of horizontally curved bridges subjected to loads recommended by three different international bridge design codes is undertaken which concludes that the Eurocode LM1 predicts higher bending moment as well as torsion with respect to other codes.